2007
DOI: 10.3389/neuro.12.004.2007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of prehension ability in an anthropomorphic neurorobotic arm

Abstract: In this paper, we show how a simulated anthropomorphic robotic arm controlled by an artificial neural network can develop effective reaching and grasping behaviour through a trial and error process in which the free parameters encode the control rules which regulate the fine-grained interaction between the robot and the environment and variations of the free parameters are retained or discarded on the basis of their effects at the level of the global behaviour exhibited by the robot situated in the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The only difference is that the real eye is controlled by three couple of muscles, whereas in our simplified model, we used two couples (i.e., inferior, superior, medial and lateral rectus). The muscles were simulated using the Hills model (Massera et al 2007(Massera et al , 2014Massera 2010). In a previous study (Gigliotta et al 2015), we demonstrated that the use of zoom actuator improves the performance of a neurorobot, controlled in velocity, in a simpler variant of cancellation task in which target stimuli disappeared as soon as they were cancelled.…”
Section: Methodsmentioning
confidence: 99%
“…The only difference is that the real eye is controlled by three couple of muscles, whereas in our simplified model, we used two couples (i.e., inferior, superior, medial and lateral rectus). The muscles were simulated using the Hills model (Massera et al 2007(Massera et al , 2014Massera 2010). In a previous study (Gigliotta et al 2015), we demonstrated that the use of zoom actuator improves the performance of a neurorobot, controlled in velocity, in a simpler variant of cancellation task in which target stimuli disappeared as soon as they were cancelled.…”
Section: Methodsmentioning
confidence: 99%
“…For each condition, the evolutionary process has been have been simulated by using Newton Game Dynamics (NGD, see: www.newtondynamics.com), a library for accurately simulating rigid body dynamics and collisions. For related approaches, see [23], [22], [24].…”
Section: Methodsmentioning
confidence: 99%
“…This in turn allows the robot to exploit sensory-motor coordination (i.e., the possibility to act in order to later experience useful sensory states) as well as the properties arising from the physical interactions between the robot and the environment. In [22] it is shown how this approach allows the robot to distinguish objects of different shapes by self-selecting useful stimuli through action, and in [23] it is shown how this approach allows for the exploiting of properties arising from the physical interaction between the robot body and the environment for the purpose of manipulating the object.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…A range sensor returns a value between zero and one commensurate with the length of the ray emitted by the sensor. Clearly these range sensors detract from the anthropomorphic aspect of the robot, but as the goal of the current work is to demonstrate the reasons for co-optimization of morphology and control rather than evolve a realistic robot, this is a minor detail: As has been shown previously [14,27,42], it is possible to evolve object manipulation for anthropomorphic robot arms without range sensors. The shoulder contains a proprioceptive sensor that measures the sagittal rotation of the arm: High positive values indicate the arm is raised, values near zero indicate the arm is horizontal, and high negative values indicate the arm is rotated downward.…”
Section: Robot Morphologymentioning
confidence: 99%
“…Grasping requires the robot to minimize the distance between its fingers and the object, lifting requires it to maximize the vertical displacement of the object, and active perception requires it to interact with objects of different shapes in order to distinguish between them. Object manipulation has been previously studied in robotics (e.g., [14,27,21,46,42]), and methods for enabling a robot to perform multiple behaviors simultaneously and in sequence constitute a popular area of study (e.g., [46]). Here, however, the goal is not to demonstrate that a robot can accomplish these tasks, but rather the task domain is used to show that there is a positive correlation between the likelihood of successfully performing complex tasks and the amount of the robotʼs morphology placed under evolutionary control.…”
Section: Task Environmentmentioning
confidence: 99%